PENGARUH KETERAMPILAN, MOTIVASI DAN BANTUAN USAHA TERHADAP KINERJA INDUSTRI KECIL MENENGAH (IKM) MEUBEL DI KABUPATEN TOJO UNA-UNA - Haeruddin Haeruddin (Katalogis, 2018)
The aims of this research are:1) to determine and analyze simultaneous influence of skills, motivation, and suppurting fund the performance of small ang middle furniture industries in Tojo Una-Una Regency; 2) to determine and analyze simultaneous influence of skills the performance of small ang middle furniture industries in Tojo Una-Una Regency; 3) to determine and analyze simultaneous influence of motivation the performance in of small ang middle furniture industries in Tojo Una-Una Regency; 4) to determine and analyze simultaneous influence suppurting fund  the performance in of small ang middle furniture industries in Tojo Una-Una Regency. This is a axplanatory research, this study explains the causality between the independent and dependent variables, which involves 38 respondents selected by using census sample method. Based on the result of multiple Linear Regressions, this research concludes that: 1) Skills, motivation, and Supporting fund simultaneously affect the employees’ performance of small ang middle furniture industries in Tojo Una-Una  Regency, both positively and significantly; 2) Skills  positively and significantly affect the employees’ performance of small ang middle furniture industries in Tojo Una-Una  Regency; 3) motivation  positively and significantly affects the employees’ performance of small ang middle furniture industries in Tojo Una-Una Regency; and 4) Supporting fund not positively and not significantly affect the employees’ performance of small ang middle furniture industries in Tojo Una-Una Regency.